Towards automated restructuring of object oriented systems - Trifu, Adrian Ioan Alexandru (KIT Scientific Publishing, 2008)
The work introduces a method for diagnosing design flaws in object oriented systems, and finding meaningful refactorings to remove such flaws. The method is based on pairing up a structural pattern that is considered pathological (e.g. a code smell or anti-pattern) with a so called design context. The design context describes the design semantics associated to the pathological structure, and the desired strategic closure for that fragment. The process is tool supported and largely automated.